Respuesta :

Answer:

The correct option is C

Step-by-step explanation:

We have given the roots -6, 1 and 4.

Write down the roots:

x= -6 , x=1 , x=4

Rewrite the roots as an expression:

x+6=0

x-1=0

x-4=0

Now we have the following expressions:

=(x+6)(x-1)(x-4)

Now Multiply the terms:

=(x²-x+6x-6)(x-4)

=(x²+5x-6)(x-4)

=x(x²+5x-6) -4(x²+5x-6)

=x³+5x²-6x-4x²-20x+24

Solve the like terms:

=x³+x²-26x+24

Thus the correct option is C....

Answer:

aaaaaaaa top one wrong

Step-by-step explanation:

ACCESS MORE